Thinking from the Yamanote: space, place and mobility in Tokyo's past and present. Issue 2 (3rd April 2018) - Pendleton, Mark; Coates, Jamie
Abstract: Tokyo's Yamanote train line has been at the centre of Japan's modernisation project and continues to define socio-spatial relations within the city today. Within this special issue of Japan Forum, we trace the contours of the Yamanote line, exploring its role as a form of mobility that creates temporalities, spaces and boundaries, and the modes of intimacy and estrangement such dynamics produce. The papers within this special issue were developed out of discussions held at the Chicago AAS conference 2015. That year marked the 130th anniversary of the line's initial opening and the ninetieth anniversary of the completion of the loop. A focus on the Yamanote line provided us with fruitful reflections on migration and marginalisation, the way space is imagined and represented in the city, and how everyday life is both disciplined and disrupted. These reflections are included throughout the contributions within this special issue as they relate to Japan; however, they also attest to the continued importance of Japan as a site to reflect on broader socio-historical questions. As we show in this special issue, thinking from the Yamanote line not only allows us to think about Tokyo or Japan, but also affords attention to wider questions relevant to urban life more generally.